Temporal Variability of Escherichia coli Diversity in the Gastrointestinal Tracts of Tanzanian Children with and without Exposure to Antibiotics - Taylor K. S. Richter (American Society for Microbiology, 2018)
ABSTRACT The stability of the Escherichia coli populations in the human gastrointestinal tract is not fully appreciated, and represents a significant knowledge gap regarding gastrointestinal community structure, as well as resistance to incoming pathogenic bacterial species and antibiotic treatment. The current study examines the genomic content of 240 Escherichia coli isolates from 30 children, aged 2 to 35 months old, in Tanzania. The E. coli strains were isolated from three time points spanning a six-month time period, with and without antibiotic treatment. The resulting isolates were sequenced, and the genomes compared. The findings in this study highlight the transient nature of E. coli strains in the gastrointestinal tract of these children, as during a six-month interval, no one individual contained phylogenomically related isolates at all three time points. While the majority of the isolates at any one time point were phylogenomically similar, most individuals did not contain phylogenomically similar isolates at more than two time points. Examination of global genome content, canonical E. coli virulence factors, multilocus sequence type, serotype, and antimicrobial resistance genes identified diversity even among phylogenomically similar strains. There was no apparent increase in the antimicrobial resistance gene content after antibiotic treatment. The examination of the E. coli from longitudinal samples from multiple children in Tanzania provides insight into the genomic diversity and population variability of resident E. coli within the rapidly changing environment of the gastrointestinal tract of these children. IMPORTANCE This study increases the number of resident Escherichia coli genome sequences, and explores E. coli diversity through longitudinal sampling. We investigate the genomes of E. coli isolated from human gastrointestinal tracts as part of an antibiotic treatment program among rural Tanzanian children. Phylogenomics demonstrates that resident E. coli are diverse, even within a single host. Though the E. coli isolates of the gastrointestinal community tend to be phylogenomically similar at a given time, they differed across the interrogated time points, demonstrating the variability of the members of the E. coli community in these subjects. Exposure to antibiotic treatment did not have an apparent impact on the E. coli community or the presence of resistance and virulence genes within E. coli genomes. The findings of this study highlight the variable nature of specific bacterial members of the human gastrointestinal tract.